Paradigma PARADIGMA INTEGRATIF-INTERKONEKTIF DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI MADRASAH - MUHAMMAD ISA ANSHORI; ALVIANI NUR BAITI ROHMA; WIDYA WULANDARI; DWI WULAN SARI (Raudhah - Proud To Be Professional, 2022)
The development of Islamic religious education curriculum in madrasas has become a real norm of the times that have complex problems. However, the reality is that the Islamic religious education curriculum is still unable to have a significant effect because it is still independent and reluctant to "shake hands" with other sciences. So it is necessary to have an approach that can provide insight into religious knowledge that is integrated with other scientific disciplines to help students in dealing with life's problems. The integrative-interconnective approach is an alternative to achieve this goal. This research is a qualitative research literature (library research) with descriptive analysis method. Data obtained from books, journals and documents related to the research will be collected and analyzed and then concluded objectively. The results of this study are the need for a new paradigm in the development of Islamic religious education curriculum in madrasas. Integrative-interconnectivity is a new alternative in the development of Islamic religious education curriculum in madrasas. With this approach. Then madrasas will be increasingly noticed by the community and make students spiritually pious and socially pious.